Optical fiber biosensors : device platforms, biorecognition, applications /: device platforms, biorecognition, applications. (2021) - Tosi, Daniele; Sypabekova, Marzhan; Bekmurzayeva, Aliya; Molardi, Carlo; Dukenbayev, Kanat
No abstract available